Novel Germline Variant in Tumor Suppressor SMAD3 Gene Associates with Familial Thoracic Aortic Aneurysm and Dissection Syndrome - Kankuri-Tammilehto Minna (JSciMedCentral, 2022)
Pathogenic variant (PV) in tumor suppressor gene SMAD3 (SMAD family member 3) causes dysregulated transforming growth factor-β (TGF-β) signaling. PV in SMAD3 is seen in sporadic cancers as somatic variant but also in germline variant causing hereditary TGF-β vasculopathy with aneurysm condition. The clinical picture of thoracic aortic aneurysm, dilatation or dissection (TAAD) families with SMAD3 PV has been published from the year of 2011. The phenotypic spectrum of SMAD3 PVs has not yet been fully identified. This case report shows the family with novel SMAD3 variant named c.860G>A with very high risk for aortic dissection approximately at the age of 50 years. The result of segregation analysis of the family strongly suggests that this variant is pathogenic. The main symptom in the family is aortic dilatation and aortic dissection.